Detrital zircon and apatite U-Pb geochronology of Ediacaran fossil–bearing strata spanning the late Ediacaran–Cambrian boundary in central Iran. Issue 1 (2nd January 2022) - Farjandi, Farnoosh; Vickers-Rich, Patricia; Linnemann, Ulf; Raveggi, Massimo; Hofmann, Mandy; Hall, Michael; Rich, Thomas H.
Abstract: The Neoproterozoic successions exposed in the Koushk and Chahmir areas of central Iran include both volcanic, and shallow to deep marine siliciclastic and carbonate units. We obtained detrital zircon dates from tuffaceous shales bearing Ediacaran fossils, including Corumbella, Persimedusites, ? Kimberella, ? Cloudina, and Namalia -like forms, together with a single metazoan holdfast structure from the Dargazin area of the Koushk region that correlates with the upper part of the Wedge succession dated at 555 ± 14 Ma. Zircon grains of the tuffaceous siltstones containing Corumbella, Persimedusites, ? Kimberella, ? Cloudina, Namalia -like structures, ? Spriggina, ? Pteridinium, holdfasts and algae-like branching structures in the Wedge section of the Koushk area, produced an age of 581 ± 9 Ma, whereas pyroclastic sandstones bearing Corumbella, Persimedusites, a possible holdfast, ? Pteridinium, ? Cloudina, algae-like branched structure, possible trace fossils and marine algal remains in the Chahmir area yielded an age of 541 ± 5 Ma. Zircon dates from the Dargazin and Wedge deposits are of late Ediacaran and Chahmir strata are of a late Ediacaran to early Cambrian age. Ages of the Chahmir sedimentary rocks are close to those from Dargazin. Based on our results, the maximum depositional age of the detrital zircons indicates relatively consistent sedimentation throughout the late Ediacaran and the early Cambrian, ranging from 590 to 530 Ma. Farnoosh Farjandi [ ffarjandi@swin.edu.au ], Faculty of Science, Engineering and Technology, Swinburne University of Technology, Melbourne (Hawthorn), Victoria 3122, Australia and Department of Geochemical Exploration, Geological Survey of Iran, Tehran, Iran; Patricia Vickers Rich [ prich@swin.edu.au ], Faculty of Science, Engineering and Technology, Swinburne University of Technology, Melbourne (Hawthorn), Victoria 3122, Australia and School of Earth, Atmosphere and Environment, Monash University, Melbourne (Clayton), Victoria 3800, Australia; Ulf Linnemann [ ulf.linnemann@senckenberg.de ] and Mandy Hofmann [ mandy.hofmann@senckenberg.de ], Senckenberg Naturhistorische Sammlungen Dresden, Sektion Geochronologie, 01109 Dresden, Germany; Massimo Raveggi [ massimo.raveggi@monash.edu ] and Michael Hall [ mike.hall@monash.edu ], School of Earth, Atmosphere and Environment, Monash University, Melbourne (Clayton), Victoria 3800, Australia; Thomas H. Rich [trich@museum.vic.gov.au ], Museum Victoria, Melbourne, Victoria, 3000, Australia